Early arrival of Southern Source water in the deep North Atlantic prior to Heinrich event 2 - Gutjahr, Marcus; Lippold, Jörg (Paleoceanography, 2011)
North Atlantic Deep Water ventilated the deep N Atlantic during early MIS 2 - Deep and intermediate water changes preceded Heinrich event 2 - Heinrich event 2 was the result and not the cause for AMOC ...